Taxonomic revision of the recent marine Corbulidae (Mollusca, Bivalvia) from Brazil - Arruda, Eliane P. (Zootaxa, 2020)
The present study provides a taxonomic revision of living species of Corbulidae from Brazil based on shell characters, including the examination of the type material and specimens from different collections from Brazil, USA and Europe. There are twelve species of Corbulidae in Brazil belonging to Corbula, Caryocorbula, Juliacorbula, Tenuicorbula and Varicorbula. Caryocorbula chittyana, Caryocorbula marmorata, Caryocorbula luteola and Juliacorbula bicarinata are new occurrences in Brazil. Corbula dietziana, Caryocorbula swiftiana and Caryocorbula chittyana have identical shell morphologies to species from the Eastern Pacific possibly indicating closer phylogenetic relationships. Corbula tryoni and Corbula patagonica appear to be endemic to South America. These latter species are similar to Corbulidae from the Indo-Pacific. Based on comparisons with type material, the following synonymies are suggested: Corbula uruguayensis, traditionally considered a synonym of Caryocorbula swiftiana, is a specimen in pre-accretion stage of C. patagonica, and Corbula caribaea, Corbula barratiana and Corbula kjoeriana are synonyms of Caryocorbula swiftiana. Three species have great morphological variability, C. patagonica, C. swiftiana and Juliacorbula aequivalvis; most species exhibit great post-larval ontogenetic variability.